Letter - Brooke, Eileen E.
025a-0047-001 46 KINGSWAY London W.C.2 TEL HOLBORN 6535 April 30th, 1940. Dear Mr. Tewson, On behalf of Sr. Azcárate, who is at present out of town, I write to tell you that he has now received a reply from the S.E.R.E. regarding the Spanish seamen who are being maintained in England by the T.U.C. The S.E.R.E. ask in their letter for the following information : (a) List of the men, giving names, surnames, age, civilian occupation, number in family, reason for their stay in England, date since which they have been in this country, and activities during the Spanish War. (b) List of any who may have refused to return to Spain when recalled. (c) Reason why these man have not found work at sea in the present situation. (d) Any other indications which you may feel it would be useful to give. You have, of course, already given an explanation regarding question (c). I don't know to what extent it will be possible to facilitate information on the other points, but whatever indications you may be able to give will be passed on to Paris immediately. I remain, Yours sincerely, E.E. Brooke H. Tewson, Esq., Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/25a/47